Lessons from the proposed contours of a Russia-Ukraine peace agreement: A way for China and Taiwan to coexist? - Kallio Jyrki; Mattlin Mikael (Ulkopoliittinen instituutti, 2026)
If China’s security concerns with regard to the growing US presence in its neighbourhood are not taken seriously, it could start seeing Taiwan as analogous to Ukraine, despite the obvious differences. The proposed contours of a peace agreement in Ukraine could inspire an interim settlement for the Taiwan question.